PENGARUH KOMPENSASI, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA ASHITABA ARTSHOP BALI - I Gede Muliarsa Agustinus; I Gde Bayu Surya Parwita; Ni Nyoman Suryani; Ni Wayan Ari Sudiartini (Jurnal Ilmiah Satyagraha, 2021)
Employee Performance is one of important factor, because the improvement of the organization or company depends on the human resources possessed. This study aims to determine the influence of compensation on employee performance in Ashitaba Artshop Bali, knowing the influence of work discipline on employee performance in Ashitaba Artshop Bali, also to determine the influence of job satisfaction on employee performance in Ashitaba Artshop Bali.The sample in this study were 30 respondents. The analytical tool used is multiple linear regression analysis using SPSS. Based on the results of multiple linear regression analysis that Y = 4,031  + 0,325 X1 + 0,346 X2+ 0,250 X3.. Based on test of t value regression coefficient on X1(Compensation) is 0,325 with significant level at 0,006 smaller than real level α = 0,05. This shows that compensation has a positive and significant influence on employee performance in Ashitaba Artshop Bali. While significant level of work discipline is at 0,023 real level α = 0,05. This shows that work discipline has a positive and significant influence on employee performance in Ashitaba Artshop Bali. Lastly, significant level of job satisfaction is at 0,021   real level α = 0,05. This shows that job satisfaction has a positive and significant influence on employee performance in Ashitaba Artshop Bali.